Download presentation

Presentation is loading. Please wait.

Published byBarrie Bradley Modified over 9 years ago

1
**Problems of the Day Simplify each expression. 1. (9s3t2)(−3st)**

2. 5xy2(x + y) 3. 7mn(m2 + 10mn – 2) 4. d(−3d + 5) + 15d 5. 4w(5w – 4) + 3(w2 – 2w + 6) 6. x(x + 3) – 2(x – 7)= x(x + 8) −27s4t3 5x2y2 + 5xy3 7m3n + 70m2n2 – 14mn −3d2 + 20d 23w2 – 22w + 18 x = 2

2
**Multiplying Polynomials**

Algebra 1 ~ Chapter 8.7 Multiplying Polynomials

3
**This is what is called EXPAND or EXPANDING!**

To multiply a binomial by a binomial, you can apply the Distributive Property more than once. This is what is called EXPAND or EXPANDING! (x + 3)(x + 2) = x(x + 2) + 3(x + 2) = x(x + 2) + 3(x + 2) = x(x) + x(2) + 3(x) + 3(2) = x2 + 2x + 3x + 6 = x2 + 5x + 6

4
**Example 1 – Simplify each expression**

(x + 5)(x + 1) = x(x) + x(1) + 5(x) + 5(1) = x2 + 1x + 5x + 5 = x2 + 6x + 5 This expression is completely simplified. There are no like terms to combine.

5
**Example 2 – Simplify each expression**

(y + 3)(y – 7) = y(y) + y(-7) + 3(y) + 3(-7) = y2 + (-7y) + 3y + (-21) = y2 – 4y – 21 This expression is completely simplified. There are no like terms to combine.

6
**Example 3 – Simplify each expression**

(a – 2)(a + 6) = a(a) + a(6) + -2(a) + -2(6) = a2 + 6a + (-2a) + (-12) = a2 + 4a – 12 This expression is completely simplified. There are no like terms to combine.

7
**Example 4 – Simplify each expression**

(x – 4)(x – 5) = x(x) + x(-5) + -4(x) + -4(-5) = x2 + (-5x) + (-4x) + 20 = x2 – 9x + 20 This expression is completely simplified. There are no like terms to combine.

8
**Example 5 – Simplify each expression**

(2x + 3)(6x + 5) = 2x(6x) + 2x(5) + 3(6x) + 3(5) = 12x2 + 10x + 18x + 15 = 12x2 + 28x + 15 This expression is completely simplified. There are no like terms to combine.

9
**Example 6 – Simplify each expression**

(2x + 8)(5x – 4) = 2x(5x) + 2x(-4) + 8(5x) + 8(-4) = 10x2 + (-8x) + 40x + (-32) = 10x2 + 32x – 32 This expression is completely simplified. There are no like terms to combine.

10
**Example 7 – Simplify each expression**

(3x2 – 2)(4x2 –5x+ 9) = 3x2(4x2) + 3x2(-5x) + 3x2(9) -2(4x2) + -2(-5x)+ -2(9) = 12x4 + (-15x3) + 27x2 +(-8x2) + 10x +(-18) = 12x4 – 15x3 + 19x2 +10x – 18 This expression is completely simplified. There are no like terms to combine.

11
**Ex. 8 – Find the area of each shape below.**

a.) b.) (4x – 3) (x + 4) (2x + 8) A = ½(b · h) A = ½(4x – 3)(2x + 8) = ½(8x2 + 32x – 6x – 24) = ½(8x2 + 26x – 24) A = 4x2 + 13x – 12 A = b · h A = (3x + 1)(x + 4) = 3x2 + 12x + 1x + 4 A = 3x2 + 13x + 4

12
**Lesson Wrap Up ~ Simplify each expression**

1. (x + 2)(x – 8) 2. (a – 3)(a – 9) 3. (2x – 7)(5x – 4) 4. (3x – 5)(3x + 1) 5. Find the area of a triangle whose base is (6x + 4) and height is (x – 7). x2 – 6x – 16 a2 – 12a + 27 10x2 – 43x + 28 9x2 – 12x – 5 A = 3x2 – 19x – 14

13
Assignment Study Guide 8-7 (In-Class) Skills Practice 8-7 (Homework)

Similar presentations

© 2024 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google